The Influence of Brand Image and Price Perception on Buavita Purchasing Decisions at Alfamart Kemanggisan 2 Jakarta - Ronnie, Dave Matthew; Supriyono, Supriyono (International Journal of Economics (IJEC), 2024)
This study aims to determine the effect of brand image and price perception on purchasing decisions of Buavita product at Alfamart Kemanggisan 2 Jakarta. This quantitative method research uses the population of Buavita consumers at Alfamart Kemanggisan 2 Jakarta in the last 3 months. The number of research samples was 99 people who were taken using the non-probability sampling method with purposive sampling technique. The data collection method was carried out through the distribution of conventional questionnaires and was measured using a Likert scale. The analysis used is Partial Least Square (PLS). The results of this study indicate that there is a significant influence between brand image and purchasing decisions also price perception and buying decisions of Buavita product at Alfamart Kemanggisan 2 Jakarta.